2008
DOI: 10.1212/01.wnl.0000286947.89193.f3
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of vertebrobasilar dolichoectasia

Abstract: The long-term prognosis of patients with vertebrobasilar dolichoectasia (VBD) depended mainly on the severity of the condition at diagnosis and on its evolutionary characteristics. Progression of VBD exposed patients to high risk of adverse events, especially stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
212
2
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(241 citation statements)
references
References 26 publications
9
212
2
8
Order By: Relevance
“…VFAs most commonly manifest as posterior circulation ischemic strokes, but they may also cause cranial nerve palsies, brainstem compression, obstructive hydrocephalus, and intraparenchymal or subarachnoid hemorrhage (SAH). 5,14,[18][19][20][21][22]29 VFAs have an ominous natural history with a reported mortality up to 30%. 3,24,29 Passero and Rossi reported that 43% of patients without treatment experienced anatomical progression and 60% experienced new symptoms.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…VFAs most commonly manifest as posterior circulation ischemic strokes, but they may also cause cranial nerve palsies, brainstem compression, obstructive hydrocephalus, and intraparenchymal or subarachnoid hemorrhage (SAH). 5,14,[18][19][20][21][22]29 VFAs have an ominous natural history with a reported mortality up to 30%. 3,24,29 Passero and Rossi reported that 43% of patients without treatment experienced anatomical progression and 60% experienced new symptoms.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…Approximately 43% of VBD patients, especially with rapid expansion, exacerbate during follow-up and the mortality is high [3]. The long-term prognosis of VBD is mostly associated with the severity of the condition at initial diagnosis and on its evolution characteristics, which was associated with a higher mortality and morbidity [4].…”
Section: Journal Of Neurology and Neurosciencementioning
confidence: 99%
“…The most common outcome of VBD is ischemic stroke mainly characterized by posterior cerebral ischemia [2]. Previous studies suggest that cases characterized by the diameter expansion of blood vessels are more likely to result in stroke while compression symptoms can be found more common in cases featured by tortuous expansion [3]. The most commonly symptoms are related with ischemic, hemorrhagic and mass effect of the lesion [4].…”
Section: Introductionmentioning
confidence: 99%
“…Vertebrobasilar dolichoectasia (VBD) was a clinical entity characterized by elongated, dilated and/or tortuous vertebral artery, and basilar artery (BA),1, 2, 3 ranging from 0.05% to 18% 4, 5, 6. VBD presentation includes symptoms by cerebral ischemia in the vertebrobasilar territory 2, 3, 4, 5, 6…”
Section: Introductionmentioning
confidence: 99%
“…VBD presentation includes symptoms by cerebral ischemia in the vertebrobasilar territory 2, 3, 4, 5, 6…”
Section: Introductionmentioning
confidence: 99%